Development and Acaricide Toxicity of Abamectin as A Nanoemulsion Formulation Against The Red Palm Mite Raoiella indicas - Aldosary, Naser H.; Alnajim, Ihab A.; Al-Darwish, Muhammad A. (Basrah Journal Of Date Palm Research, 2023)
The red palm mite (RPM) Raoiella indica is one of the common pests infesting date palms and may cause economic damage if left uncontrolled. Among the most widely used acaricides for controlling RPM is abamectin; however, the application of large quantities causes environmental damages. Due to the unique properties of nano-pesticides, the current study was designed to create a stable nanoemulsion of Abamectin via low-energy methods to control RPM. Eight hydrophilic-lipophilic balances (HLB) were prepared by blending different ratios of Tween 80 and Span 80 that were mixed with paraffin oil and water. HLB 9 and 11 combinations achieved homogeneity and one phase therefore two ternary phase diagrams were created, four pre-formulation points were selected ‎‎, and 35 % v/v of Abamectin was uploaded to them. Two formulations passed kinetic and thermal stability. The formulations were nanoemulsion at 54.20 and 137.45 nm with good physical characterizations. The Abamectin nanoemulsion formulations recorded the largest droplet spreading and achieved high acaricidal toxicity after spray applications against RPM compared to the normal Abamectin formulation. These findings suggest that nanoformulations of Abamectin offer the potential to increase PRM control efficiency, which can reduce costs, delay the emergence of insect resistance, and reduce side effects.